Gender differences in active ageing: Findings from a new individual-level index for European countries and health in childhood - David Steinmayr; Doris Weichselbaumer; Rudolf Winter-Ebmer (Johannes Kepler University of Linz, Department of Economics, 2019)
We use data from wave 6 of the Survey of Health, Ageing and Retirement in Europe (SHARE) to construct an individual-level index of active ageing for people aged between 50 and 90 years. We develop nine sub-indices for different dimensions, which are then aggregated to the final index. This individual-level index allows to analyze inequalities between age cohorts, dimensions, countries, and other individual-characteristics that are covered by SHARE. We focus on differences between the sexes. Overall women score lower than men with 54.9 index-points compared to 57.7 for men. We present gender differences in active ageing for some sub-populations as a showcase for this new individual-level index.
Keywords: 330